ACADEMIC PERFORMANCE OF TEACHING AND RESEARCH STAFF IN AGRICULTURAL HIGHER EDUCATION OF MOLDOVA - Liliana CIMPOIES (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Moldova traditionally relies on the agricultural sector, rural population representing one third of labor force. The agricultural education and research system in Moldova is characterized by the aging of the teaching and research staff, the reduction of the number of students below the critical level, unattractiveness of science and education for the young generation, the weak connection between education, science and production, but also the inefficiency of the institutional activity. All these represent a major danger for the sustainable development of the rural areas. The aim of this paper is to analyze the major factors affecting the academic performance of research and teaching staff in agricultural higher education of Moldova. The study is based on field surveys of academic personnel of State Agricultural University, the only agricultural higher education institution in Moldova. The data set includes 120 respondents. Main analyzed indicators are related to academic performance as: professional motivation, research activity in projects, published research results and achievements, main problems and challenges within the institution related and other relevant factors. As result, income level remains an important factor for staff motivation in achieving higher performance.